2018
DOI: 10.1038/s41524-018-0101-z
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between epidermal stem cell dynamics and dermal deformation

Abstract: We introduce a particle-based model of self-replicating cells on a deformable substrate composed of the dermis and the basement membrane and investigate the relationship between dermal deformations and stem cell pattering on it. We show that our model reproduces the formation of dermal papillae, protuberances directing from the dermis to the epidermis, and the preferential stem cell distributions on the tips of the dermal papillae, which the basic buckling mechanism fails to explain. We argue that cell-type-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
(53 reference statements)
3
20
0
Order By: Relevance
“…The previous works [49,50] are limited to the report of the upper limit for the DW factor in a single V Si defect, which is below 30%-40% depending on the crystallographic site and polytype. Most of the theoretical works are concentrated on the spin-optical properties [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…The previous works [49,50] are limited to the report of the upper limit for the DW factor in a single V Si defect, which is below 30%-40% depending on the crystallographic site and polytype. Most of the theoretical works are concentrated on the spin-optical properties [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…To answer this question, we employed mathematical modeling. The particle-based model of self-replicating cells (41,42) allowed us to visualize the dynamics of the epidermal basal layer and to establish the epidermal defects on the basement membrane. We utilized the data on the number of We finally applied this in silico model to a human setting, in which HFs are much more sparsely distributed but larger than their murine counterparts (Supplementary Table 1) and found that the progeny of HF keratinocytes are still the main contributors to subepidermal blister healing in humans (Figure 7a, 7b, Supplementary Video 4).…”
Section: Mathematical Modeling Reproduces Blister Healingmentioning
confidence: 99%
“…A mathematical model proposed for epidermal cell dynamics (41) was adapted to simulate epidermal wound healing. In this model, epidermal basal cells were represented as spherical particles, with the cell diameter set to 10 µm.…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Agent-based modelling has been very successful in studying various aspects of tissue growth, such as buckling and stem cell distribution in mammalian skin [39], formation of vascular networks [40] or wound healing [41]. For tumor growth, existing models focus on different stages of tumor progression, e.g.…”
Section: Modelmentioning
confidence: 99%